The effect of joint configuration on the strength and stress distributions of dissimilar adhesively bonded joints. (1st January 2021) - Kanani, Armin Yousefi; Hou, Xiaonan; Laidlaw, Rachael; Ye, Jianqiao
Highlight: The scarf joint provides the best performance in comparison to the lap joints, irrespective of overlap length. Increasing the overlap length was only beneficial for certain types of joints. The mechanical properties of adherends significantly affect the failure of dissimilar joints. The failure always initiates at the lower stiffness adherend-adhesive interface in dissimilar joints. Abstract: The recent increase in the use of adhesively bonded joints (ABJs) made from dissimilar adherends demands the acquisition of a better understanding of the strength and behaviour of these joints, including their failure mechanisms. Several studies have reported on such joints individually, however few have compared the performances of dissimilar ABJs with varying configurations and design parameters, in order to determine the optimal design configuration for hybrid structures. In this work, a comparative study using experimental methods and finite element analysis was conducted, focusing on four joint configurations (scarf joints, stepped-lap joints, half-lap splice joints and single-lap joints), with the aim of evaluating the ways in which their performances differ. In addition, the effects of overlap length ( L 0 ) and the mechanical properties of the adherends on the overall success of each joint were particularly closely analysed and compared. The results showed that the scarf joint provided the best performance of all the designs discussed, and it was found that increasing the overlap length was only significantly beneficial for certain joint configurations and adherend combinations. When the overlap length was increased from 12.5 mm to 25 mm, the failure load increased by 47.50% and 21.25% for the scarf and the stepped-lap joints, respectively. In comparison, the percentage increases for the half-lap splice and single-lap joints under the same conditions were less than 10%. Moreover, the mechanical properties of the adherends considerably affected the failure mechanisms of the dissimilar joints, and for all four joint configurations, the failure was initiated by a crack at the adherend-adhesive interface adjacent to the adherend with a lower modulus.